Human Factors Capstone Research at the United States Air Force Academy. (November 2019) - Tossell, Chad; Donadio, Bianca; Stewart, Amanda; Tenhundfeld, Nathan; Phillips, Elizabeth; Driggs, Jade; Haring, Kerstin; de Visser, Ewart
Prior studies have shown research projects completed as part of undergraduate curricula are not only becoming more commonplace, but they also provide substantial benefit to student learning. Given this evidence, the Department of Behavioral Sciences and Leadership (DFBL) at the United States Air Force Academy has recently required capstone research for every cadet in the behavioral sciences major. The purpose of this paper is to describe how the human factors program has structured the capstone experience within the Warfighter Effectiveness Research Center (WERC) in DFBL. Even though some research experience has been a longstanding requirement in the human factors program for many years, the capstone sequence has led to a shift in what undergraduates are accomplishing in and out of the classroom. In addition to examples of current projects, we provide several recommendations for academic institutions to implement capstone projects.